A complex network study on Guangdong-Hong Kong-Macao Greater Bay Area based on economic development index - Feng, Qingxiang; Zhu, Sha; Lai, Fujun (Frontiers in Physics, 2022)
City cluster, the most advanced spatial organization for urban development in the mature stage, is an important carrier for regional economic development. This paper researched into the correlation of economic development changes among cities in the Guangdong-Hong Kong-Macao Greater Bay Area through a new complex network approach. First, Principal Component Analysis was adopted to downscale the economic indicators of each city in the Greater Bay Area, and then we construct an economic development index on this basis; Second, through a TVS-VAR-SV model, an complex network of economic development changes within the city clusters in the Greater Bay Area was built based on the economic development index of each city mentioned above. It can be concluded from the study that Macao, firstly, is the biggest beneficiary of the complex network. Secondly, the most important node in the network is Guangzhou, whose development has a multiply effect on the development of the whole system. Thirdly, Hong Kong and Shenzhen enjoy the highest level of economic development, but their spillover effect on the city cluster system is much lower than that of Guangzhou.